2020
DOI: 10.1002/elan.202000025
|View full text |Cite
|
Sign up to set email alerts
|

Highly Hydrophilic Polymer Composite Modified Electrode for Trace Copper Detection Based on Synergetic Electrostatic Attractions and Chelating Interactions

Abstract: A new electrochemical sensor for Cu 2 + detection by square wave voltammetry with high sensitivity has been constructed, based on a composite of sodium carboxymethyl cellulose and Nafion. Starting from these two polymers that are rich of hydrophilic groups in backbones, a highly negative-charged composite has been easily prepared, which displays outstanding ability to adsorb and enrich Cu 2 + onto the electrode surface through both electrostatic attractions and chelating interactions. After optimizing test con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Taken together, these results demonstrated that the VMSF- g -CS/GCE obtains excellent sensing performance to Cu 2+ . The reason is inferred as follows: (1) the synergistic enrichment effects of negative surface charges of VMSF and CS, (2) the complexation effect with Cu 2+ of CS could improve the power of enrichment analysis of Cu 2+ …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Taken together, these results demonstrated that the VMSF- g -CS/GCE obtains excellent sensing performance to Cu 2+ . The reason is inferred as follows: (1) the synergistic enrichment effects of negative surface charges of VMSF and CS, (2) the complexation effect with Cu 2+ of CS could improve the power of enrichment analysis of Cu 2+ …”
Section: Resultsmentioning
confidence: 99%
“…After the modification of VMSF, the dissolving peak current of VMSF/GCE significantly increased. It could be due to the enrichment of positively charged molecules and ions from the negative surface of VMSF . When CS was directly modified on the surface of VMSF, the peak currents of Cu 0 at VMSF-CS/GCE were much higher due to the increased active sites and functional groups of CS, which made VMSF-CS to exhibit superior enhancement toward Cu 2+ .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is of great significance to detect Cu(II) accurately and quickly. There are many detection methods for Cu(II), chiefly including colorimetric analysis [3], atomic absorption spectrometry (AAS) [4], inductively coupled plasma mass spectrometry (ICP-MS) and electrochemical techniques [5]. Among them, the electrochemical technique for Cu(II) detection of differential pulse anodic stripping voltammetry (DPASV) has been widely utilized because of its enhanced faradic current and decreased non-faradic charging current [6].…”
Section: Introductionmentioning
confidence: 99%